2017
DOI: 10.2131/fts.4.95
|View full text |Cite
|
Sign up to set email alerts
|

Repeated-dose ocular instillation toxicity study: a survey of its study design on the basis of common technical documents in Japan

Abstract: -A repeated-dose ocular instillation toxicity study is a type of general toxicity study having unique design characteristics of species selection and administration methods, because the test article, an eye drop formulation, is instilled in the eyes. The present survey was conducted to reveal the current status of the design of repeated-dose ocular instillation toxicity studies. Information on study design was collected from the common technical documents of 21 eye-drop drugs approved in the last decade in Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…51 The Japanese white rabbit, employed in this study, is also used experimentally including in ocular safety evaluations. 3,52 The growth in eyeball axial length, eyeball weight, and eyeball volume; lens thickness, lens weight, and lens volume; and vitreous weight and vitreous volume are similar between New Zealand and Japanese white rabbits. 24 No apparent histological differences in the eyes from PND1 to 14 were noted between this study and previous studies on the New Zealand white rabbit.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…51 The Japanese white rabbit, employed in this study, is also used experimentally including in ocular safety evaluations. 3,52 The growth in eyeball axial length, eyeball weight, and eyeball volume; lens thickness, lens weight, and lens volume; and vitreous weight and vitreous volume are similar between New Zealand and Japanese white rabbits. 24 No apparent histological differences in the eyes from PND1 to 14 were noted between this study and previous studies on the New Zealand white rabbit.…”
Section: Discussionmentioning
confidence: 96%
“…Ophthalmic drugs are sometimes used in children. 32 When safety evaluations of ophthalmic drugs are conducted, rabbits are generally used in nonclinical toxicology studies, 1 3 including for intravitreal injection drugs. 33,34 There are several reports of juvenile rabbits being used for toxicological evaluations for topical ocular drugs or intravitreal injection agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dutch rabbit is a major breed used in ocular toxicity studies (Kurata et al, 2017). In rabbits, sexual maturity occurs earlier in females than in males, and it has been reported that smaller breeds mature earlier than large ones; Dutch rabbits mature at 4 to 5 months of age and NZW rabbits mature at 5 to 7 months of age (Hillyer, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…These formulations may affect the eyes because of their morphological or functional immaturity in children and influence the postnatal ocular development. Rabbits are generally used for safety evaluation of ophthalmic drugs (Attar et al 2013; Kurata et al 2017). An increase of Na + /K + -ATPase pump density in the rabbit corneal endothelium occurs for up to 30 days after birth (Stiemke, Edelhauser, and Geroski 1991).…”
mentioning
confidence: 99%